Socioeconomic and intraoral polarization of untreated caries and tooth loss among male adolescents - Priscila STONA; Paulo Floriani KRAMER; Fabiana VARGAS-FERREIRA; Lívia Mund de AMORIM; Elisa Maria de Rosa Barros COELHO; Carlos Alberto FELDENS (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract The aim of this study was to investigate the intraoral distribution of untreated caries and tooth loss and estimate the impact of different socioeconomic factors on the occurrence of these outcomes. A cross-sectional study was conducted with 652 18-year-old male adolescents from the city of Sapucaia do Sul, Brazil, who conscripted for military service. The participants answered a questionnaire addressing sociodemographic variables. Two trained and calibrated examiners performed the clinical examinations for the diagnosis of dental caries using the criteria of the World Health Organization. Tooth group and adolescent were the units of analysis for the primary outcomes of the study. Poisson regression analysis with robust variance was performed, with the calculation of crude and adjusted prevalence ratios (PR) and 95% confidence intervals (CI). The prevalence of caries experience and untreated caries was 70.2% and 39.3%, respectively, and 9.4% of the adolescents had missing teeth. Sixty-seven percent of the untreated caries and 98.8% of missing teeth were in first molars. The probability of dental caries and tooth loss was significantly higher among adolescents with less schooling (PR = 2.56; 95%CI: 1.97-3.32 and PR = 3.28; 95%CI: 1.61-6.65, respectively) and those whose mothers had less schooling (PR = 1.31; 95%CI: 1.03-1.67 and PR = 2.30; 95%CI: 1.18-4.50, respectively). In conclusion, the occurrence of untreated dental caries and tooth loss was concentrated in the first molars of adolescents. Moreover, the prevalence of both conditions was higher among adolescents with low schooling and whose mothers had low schooling, reflecting the strong intraoral and socioeconomic polarization of these outcomes.